2020
DOI: 10.3390/life10110262
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis IRIS: Pathogenesis, Presentation, and Management across the Spectrum of Disease

Abstract: Antiretroviral therapy (ART), while essential in combatting tuberculosis (TB) and HIV coinfection, is often complicated by the TB-associated immune reconstitution inflammatory syndrome (TB-IRIS). Depending on the TB disease site and treatment status at ART initiation, this immune-mediated worsening of TB pathology can take the form of paradoxical TB-IRIS, unmasking TB-IRIS, or CNS TB-IRIS. Each form of TB-IRIS has unique implications for diagnosis and treatment. Recently published studies have emphasized the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 176 publications
(306 reference statements)
1
44
0
1
Order By: Relevance
“…"s Notably, the overwhelming complexity of TB-IRIS immunopathogenesis impedes the attainment of accurate predictive and diagnostic methods, thus hindering appropriate patient care and disease management. Currently, a TB-IRIS diagnosis is mainly based on clinical presentation and the initial response of the underlying TB infection to ATT, with a paradoxical deterioration after ART initiation determine from both clinical assessment and imaging methods (such as chest X ray and computed tomography) (23). Therefore, major efforts have been devoted to the identification of prediction and diagnostic biomarkers to enhance TB-IRIS management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…"s Notably, the overwhelming complexity of TB-IRIS immunopathogenesis impedes the attainment of accurate predictive and diagnostic methods, thus hindering appropriate patient care and disease management. Currently, a TB-IRIS diagnosis is mainly based on clinical presentation and the initial response of the underlying TB infection to ATT, with a paradoxical deterioration after ART initiation determine from both clinical assessment and imaging methods (such as chest X ray and computed tomography) (23). Therefore, major efforts have been devoted to the identification of prediction and diagnostic biomarkers to enhance TB-IRIS management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…While corticosteroids remain the only trial-supported medication for the prevention and management of TB-IRIS, biologic medicines that directly target the immunological pathology are gaining traction. TB-IRIS, particularly in its unmasking form, is still poorly understood, and further research is needed to verify biomarkers for diagnosis, as found by [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Glucocorticoids are also one of the mainstays of TB-IRIS management; use of other agents like anakinra and anti-TNFα have been also reported in steroid-resistant cases [ 19 , 20 ]. Of note, the patient presented IRIS even if ART was started seven weeks after anti-TB drugs.…”
Section: Discussionmentioning
confidence: 99%